Traditional Games for Establishing Respect Attitude - Dhani Agusni Zakaria; Silvy Juditya; Sumbara Hambali; Sutiswo Sutiswo; Ruslan Rusmana (Universitas PGRI Palembang, 2022)
The purpose of this study was to determine the formation of student respect through traditional games. The research method used is an experimental research design using a one group pretest-posttest design. The instrument used to collect research data is to use a questionnaire. The population in the study were all students of class V-A SDN Cipagalo 01, with the sampling technique using total sampling, the sample in this study was the entire population with a total of 25 students. After doing the treatment and collecting data, the results of the study showed that the average value of students' respect attitude between the initial test and the final test there was a significant difference after learning through traditional games. From the results of the t-test analysis, it was also found that the t-count significance value of 12.53 was greater than the t-table 1.71 (12.53>1.71), which means that it can be said that through traditional games the attitude of respect for students can be more formed. The conclusion is that traditional games have a significant influence on the formation of respect for students in grades V-A at SDN Cipagalo 01. Now is the time when we must be able to preserve traditional games, it is appropriate as educators to introduce children to traditional games even though in the current age of globalization, especially from an early age, child development is very much needed for the sake of children's physical and mental development. the role of parents to accompany their children is very important for the future of a child.